Study of Teacher Education in Pre-Independence India - Sharma, Dr. N .R. (Innovative Research Thoughts, 2017)
Pre-independence India, like the rest of the nation, saw teaching as one of the most honourable professions. The country's teacher preparation programmes are among the best in the world. Teachers were held in high regard and valued by their students. The tasks assigned to them were carried out with the greatest care and ingenuity. We made certain they had the necessary credentials and would be able to accomplish the goals set forth for them. Pre-independent India recognised the importance of teacher education. When instructors had the necessary skills and talents, they were thought to be able to transfer enough information to their pupils and promote the well-being of the community, according to this belief. Among the many topics covered in this investigation are the history of Indian teacher education, teacher training in pre-independence India, the Upanishad period, the Buddhist era, the mediaeval era, and the contemporary age.